Oxygen and animal evolution: Did a rise of atmospheric oxygen "trigger" the origin of animals?. (22nd September 2014) - Mills, Daniel B.; Canfield, Donald E.
<x xml:space="preserve">Abstract</x> Recent studies challenge the classical view that the origin of animal life was primarily controlled by atmospheric oxygen levels. For example, some modern sponges, representing early‐branching animals, can live under 200 times less oxygen than currently present in the atmosphere – levels commonly thought to have been maintained prior to their origination. Furthermore, it is increasingly argued that the earliest animals, which likely lived in low oxygen environments, played an active role in constructing the well‐oxygenated conditions typical of the modern oceans. Therefore, while oxygen is still relevant to understanding early animal evolution, the relationships between the two might be less straightforward than previously thought.